2023
DOI: 10.1002/acm2.14003
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reliability of a commercial treatment planning system in nontarget regions in modern prostate radiotherapy

Abstract: Background:The currently available treatment planning systems (TPSs) are neither designed nor intended for accurate dose calculations in nontarget regions. The aim of this work is to quantify the accuracy and reliability of nontarget doses calculated by a commercially available TPS. Methods: Nontarget doses calculated by the collapsed cone (CC) (v5.2) algorithm implemented in the RayStation (v6) TPS were compared to measured values. Different scenarios were investigated, from simple static fields to intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…This is called the skin-sparing effect of highenergy photon beams. Although TPS can accurately estimate the dose given to the target volume and OARs, studies have shown that TPS cannot accurately calculate the surface dose (Danckaert et al, 2023). The accuracy of TPSs in calculating surface dose has been reported by various researchers on inhomogeneous phantoms There is a lack of confidence in the surface dose calculation of TPS.…”
Section: Introductionmentioning
confidence: 99%
“…This is called the skin-sparing effect of highenergy photon beams. Although TPS can accurately estimate the dose given to the target volume and OARs, studies have shown that TPS cannot accurately calculate the surface dose (Danckaert et al, 2023). The accuracy of TPSs in calculating surface dose has been reported by various researchers on inhomogeneous phantoms There is a lack of confidence in the surface dose calculation of TPS.…”
Section: Introductionmentioning
confidence: 99%